Exploring the relationship between self-care agency and quality of life in adults with diabetes: A cross-sectional study - Kei Takahashi; Chizuko Takeishi; Chiyo Tsutsumi; Tomomi Nakao; Yuichi Sato; Yuji Uchizono; Kiyohide Nunoi; Yasunori Tabira; Yasuko Shimizu (PLoS ONE, 2025)
Self-care agency is the ability to perform self-care. Clarifying the factors of self-care agency that are related to quality of life can help determine the most effective nursing support. This cross-sectional study of patients with type 1 or type 2 diabetes aimed to explore the relationship between self-care agency and quality of life in adults with diabetes. Using a selective sampling method, we conducted a questionnaire survey using the Instrument of Diabetes Self-Care Agency and the SF-12 Health Survey. After identifying items related to quality of life from single regression and correlation analyses, multiple regression analyses were performed. There were 139 respondents, with an average age of 62.8 ± 11.7 years, of whom 71 were men (51.0%) and 117 had type 2 diabetes (84.1%). The average self-care agency score was 153.6 ± 22.5 points. Based on the results of the single regression analysis, age, sex, HbA1c, and BMI were selected as adjustment factors. Multiple regression analyses showed that the “ability to cope with stress” was related to the role/social component summary of health-related quality of life (β = 0.40, p < 0.01). The association between self-care agency and the mental component summary differed by age and sex, while “ability to cope with stress” was commonly related to this component across all groups (β = 0.39–0.70, p < 0.05). The “ability to make the most of the support available” (β = 0.37–0.52, p < 0.05) and the “ability to self-manage” (β = 0.51–0.56, p < 0.01) were also related to this component in the 65-and-over group. No factors of self-care agency were related to the physical component summary of health-related quality of life. The results suggest that nurses can clarify the type of support that will lead to improved quality of life by evaluating patients’ self-care agency.